2019
DOI: 10.3389/fpsyg.2019.00702
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Negative Feedback on Positive Beliefs in Self-Deception

Abstract: In the present study, we applied the forward-looking paradigm to examine how positive beliefs appear in self-deception and to further reveal the influence of negative feedback on positive beliefs to decrease self-deception. In Experiment 1, the answer group (with answer hints provided below the test material) and the control group (without answer hints) completed two tests. Participants estimated their Test 1 scores, predicted their performance on the upcoming Test 2 without answer hints, and completed Test 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…For example, Gramzow et al [22] found that positive illusions about one's GPA were negatively associated with actual future academic performance. Similarly, several studies [20,36,71] using a clever experimental design demonstrated similar negative consequences of SDE for learning, such that individuals who had taken a test with a visible answer key predicted infated test scores on a subsequent test where no answer key would be visible. In the absence of SDE, the researchers reasoned that there would be no diference in predicted scores between the experimental group and control group (who had no answer key) because the experimental group would accurately take into account the boost in initial performance from the answer key that would no longer be available on the future test.…”
Section: Te Maladaptiveness Of Sde 231 Learning and Problem-solving C...mentioning
confidence: 87%
See 1 more Smart Citation
“…For example, Gramzow et al [22] found that positive illusions about one's GPA were negatively associated with actual future academic performance. Similarly, several studies [20,36,71] using a clever experimental design demonstrated similar negative consequences of SDE for learning, such that individuals who had taken a test with a visible answer key predicted infated test scores on a subsequent test where no answer key would be visible. In the absence of SDE, the researchers reasoned that there would be no diference in predicted scores between the experimental group and control group (who had no answer key) because the experimental group would accurately take into account the boost in initial performance from the answer key that would no longer be available on the future test.…”
Section: Te Maladaptiveness Of Sde 231 Learning and Problem-solving C...mentioning
confidence: 87%
“…Tere was also a signifcant interaction between dispositional SDE and the experimental manipulation, such that dispositional self-enhancers were especially prone to taking credit for their answer-key-infated performance [20]. Furthermore, it has been shown that monetary incentives for accurate predictions of performance on the second test do not temper SDE [4], and though corrective feedback can briefy lessen SDE [36], it can be easily reinstated [71].…”
Section: Te Maladaptiveness Of Sde 231 Learning and Problem-solving C...mentioning
confidence: 99%
“…We utilized the “The Prospective Paradigm” to measure participants’ self-deceptive behavior. 18 , 22 , 23 The discrepancy between actual and anticipated performance on the prospective paradigm suggested self-deception. 41 This paradigm consists of 120 red dot plots administered in two separate tests, referred to as Test 1 and Test 2.…”
Section: Methodsmentioning
confidence: 99%
“…Self‐deception was observed only when feedback on a performance was vague (Sloman, Fernbach, & Hagmayer, 2010). Further, self‐deception decreased when people received clear negative feedback (Liu et al, 2019).…”
Section: The Current Studymentioning
confidence: 99%